THE DIGITAL ARCHITECTURE OF FINANCIAL INCLUSION: THE INTEGRATED IMPACT OF FAST PAYMENTS, DIGITAL LITERACY, AND TRUST - Nusratov Azizbek San’atillayevich (Ecominds Press, 2025)
The expansion of the digital platform ecosystem is driving endogenous growth in financial inclusion indicators through structural reductions in transaction costs and increased network effects, with payment potential and financial literacy determinants playing a central role. This paper formalizes the conceptual mechanism of inclusion in terms of platform coverage → (literacy; trust) → use → digital footprint →→ access to credit, offers a framework of measurements, and summarizes the evidence-based context for both global (Findex, BIS/CPMI, GSMA, OECD/INFE) and Uzbekistan. The results show that an education-by-design approach, interoperability of fast payment systems, and tariff transparency are crucial suffocators in bridging the gap and increasing the depth of inclusion. Meanwhile, the average low level of digital financial literacy (~53/100 on average) underscores the need to modulate political interventions within the platform itself.
Keywords: Financial inclusion, digital platforms, fintech, fast payments, mobile money, financial literacy, cybersecurity, interoperability.